Analisis Kinerja Rumah Sakit Dengan Pendekatan Metode Balanced Scorecard - Dissa Elvaretta (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the performance of Regional Hospital X by Balanced Scorecard Approach Method. This research was conducted by the method of operational research with the analysis of qualitative and quantitative data using a single case study on Regional Hospital X. As a government-owned hospital, Regional Hospital X should aim to provide good service to customers. Therefore, it is necessary to measure non-financial aspects instead of measuring financial aspects only. Measurement of performance using the Balanced Scorecard method covering four perspectives: financial, customer, internal business processes, learning and growth. The results showed that the performanced of Regional Hospital X is good enough seen from four perspective of Balanced Scorecard Method Approach.